Diversity in striatal synaptic circuits arises from distinct embryonic progenitor pools in the ventral telencephalon - van Heusden, F; Macey-Dare, A; Gordon, J; Krajeski, R; Sharott, A; Ellender, T (Cell Press, 2021)
Synaptic circuits in the brain are precisely organized, but the processes that govern this precision are poorly understood. Here, we explore how distinct embryonic neural progenitor pools in the lateral ganglionic eminence contribute to neuronal diversity and synaptic circuit connectivity in the mouse striatum. In utero labeling of Tα1-expressing apical intermediate progenitors (aIP), as well as other progenitors (OP), reveals that both progenitors generate direct and indirect pathway spiny projection neurons (SPNs) with similar electrophysiological and anatomical properties and are intermingled in medial striatum. Subsequent optogenetic circuit-mapping experiments demonstrate that progenitor origin significantly impacts long-range excitatory input strength, with medial prefrontal cortex preferentially driving aIP-derived SPNs and visual cortex preferentially driving OP-derived SPNs. In contrast, the strength of local inhibitory inputs among SPNs is controlled by birthdate rather than progenitor origin. Combined, these results demonstrate distinct roles for embryonic progenitor origin in shaping neuronal and circuit properties of the postnatal striatum.